Steel sheet having excellent corrosion properties after press hardening and method for manufacturing same
By adopting a specific composition of aluminum-based metal coating on the steel plate and forming an alloy layer during the press hardening process, the problem of microcracks and the paint step that requires sand grinding during the press hardening process of zinc coating is solved, and the problem of sand grinding operation is achieved. Good corrosion performance and cathode protection.
Patent Information
- Application Number
- CN202380052406.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-04
- Filing Date
- 2023-08-01
- Publication Date
- 2025-02-21
AI Technical Summary
During the press hardening process, zinc-coated steel plates are prone to microcracks, and the paint step requires sand grinding, which affects corrosion performance. Meanwhile, aluminum-based coatings lack cathodic protection.
The coating is deposited by a hot dip galvanizing process using an aluminum-based metal coating containing 7.5% to 9.0% zinc, 1.1% to 7.0% silicon, 1.1% to 8.0% magnesium, up to 3.0% iron and up to 0.02% impurities, and the coating is deposited by a hot dip galvanizing process and During the press hardening process, alloy layer with high corrosion resistance, wear resistance, wear resistance and fatigue resistance is formed.
In the absence of sand grinding operation, the components treated by phosphating have good corrosion performance and provide cathodic protection, which improves the overall performance of the components.
Smart Images

Figure CN119497759A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for producing a hardened component starting from a steel sheet coated with a metallic coating. The component has good properties with regard to decorative corrosion resistance after painting. The invention is particularly well suited for the production of motor vehicles. Background Art
[0002] In recent years, the use of coated steels in hot stamping processes for the forming of components has become important, especially in the automotive industry. The manufacture of such components may include the following main steps:
[0003] - coating of steel sheets by hot dipping,
[0004] - trimming or cutting to obtain blanks,
[0005] - heating the blank to obtain alloying of the steel matrix with the coating and austenitization of the steel,
[0006] -The components are press hardened to obtain a predominantly martensitic structure.
[0007] Due to the alloying of the coating with the steel substrate, which has the effect of creating an intermetallic alloy with a high melting temperature, a blank with such a coating can be heated within the temperature range where austenitization of the metal substrate occurs, allowing further hardening by quenching.
[0008] The hardened components may be coated with a zinc-based coating or an aluminum-based coating.
[0009] Zinc-based coatings are often used because they allow protection against corrosion due to barrier protection and cathodic protection. Sacrificial cathodic protection is based on the fact that zinc is a less noble metal than steel. Therefore, if corrosion occurs, zinc is consumed in preference to steel.
[0010] However, when such zinc-coated steel sheets are subjected to a press hardening process (e.g. by hot stamping), microcracks propagating from the coating are observed in the steel. Furthermore, the painting step of the zinc-coated hardened parts requires a sanding operation prior to the phosphating treatment due to the presence of a weak oxide layer at the surface of the parts.
[0011] Aluminum-based coatings have good suitability for painting. They allow protection by barrier effect and can be welded. However, they do not allow cathodic protection or they have very low cathodic protection. Summary of the invention
[0012] The object of the present invention is to provide a coated steel sheet providing cathodic protection and a suitable method for producing press-hardened components having good corrosion properties after phosphating without a prior sanding operation.
[0013] This is achieved by the steel sheets according to claims 1 to 3 .
[0014] Another object of the present invention is the manufacturing method of claim 4.
[0015] The invention also covers a press-hardened component coated with a metallic coating having an oxide layer on top of the coating according to claims 5 to 9.
[0016] A final object of the invention is the use of such a coated component according to claims 10 to 12 for the production of motor vehicles.
[0017] Other features and advantages of the present invention will become apparent from the following detailed description of the invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] To illustrate the invention, various embodiments and tests of non-limiting examples will be described with particular reference to the following drawings obtained by scanning electron microscopy at a magnification of 500 times:
[0019] - Figure 1 The homogeneous structure according to the invention is shown by observation of a cross section of a metallic coating after heat treatment on a 1.5 mm thick steel sheet with a coating comprising 8% by weight of zinc (Test 8).
[0020] - Figure 2 An inhomogeneous structure not according to the invention is shown by observation of a cross section of a metallic coating after heat treatment on a 1.5 mm thick steel sheet having a coating comprising 15% by weight of zinc (Test 12). DETAILED DESCRIPTION
[0021] The present invention relates to a steel sheet coated with a metal coating, the metal coating comprising by weight 7.5% to 9.0% zinc, 1.1% to 7.0% silicon, 1.1% to 8.0% magnesium, up to 3.0% iron, and up to 0.02% unavoidable impurities, the balance being aluminum.
[0022] Preferably, the coating comprises, by weight, 2.0% to 4.0% silicon and 1.1% to 4.0% magnesium, advantageously 1.5% to 2.5% magnesium.
[0023] Optionally, the coating comprises an additional element selected from Ni, Zr, Hf, Sr, Sb, Pb, Ti, Ca, Mn, Sn, La, Ce, Cr, or Bi, the content of each additional element by weight being less than 0.3 wt.%. In a preferred embodiment, up to 100 ppm of calcium is added.
[0024] Finally, the coating may contain up to 0.02%, preferably up to 0.01%, of unavoidable impurities.
[0025] The steel sheet according to the present invention can be manufactured by hot-dip galvanizing in a bath, the temperature of which is set to 600°C to 700°C, preferably 620°C to 650°C.
[0026] During the wiping process by the air knife, the coating weight was set at 50 g / m2 for both sides of the steel plate in total. 2 Up to 500g / m 2 , can be 80g / m 2 Up to 150g / m 2 , and preferably 100g / m 2 Up to 120g / m 2 within the range.
[0027] Before being coated, the steel sheet according to the invention can be obtained by hot rolling and optionally cold rolling according to the desired thickness, which can be, for example, 0.5 mm to 3.0 mm.
[0028] The steel substrate to be coated may have any suitable composition, depending on the desired final properties. When the steel is to be used for press hardening, its composition is preferably as described below.
[0029] The coated steel sheet according to the invention can be used in particular in a press hardening method. In particular, it can be used within the framework of the production method of a press hardened component according to the invention.
[0030] The method according to the invention comprises the following steps:
[0031] A) providing a coated steel sheet according to the invention,
[0032] B) cutting the coated steel sheet to obtain blanks,
[0033] C) heat treating the blank at a temperature of 840° C. to 950° C. to obtain a fully austenitic microstructure in the steel,
[0034] D) Transfer the blank into the pressing tool,
[0035] E) press-hardening the blank to obtain a component,
[0036] F) Cooling the component obtained in step E) to obtain a press-hardened component.
[0037] Any steel can advantageously be used within the framework of the invention in step A. However, in the case where steels with high mechanical strength are required, in particular for parts of the structure of motor vehicles, steels with a tensile resistance higher than 500 MPa, advantageously between 500 MPa and 2000 MPa, before or after heat treatment can be used. The weight composition of the steel plate is preferably as follows: 0.03% ≤ C ≤ 0.50%; 0.3% ≤ Mn ≤ 3.0%; 0.05% ≤ Si ≤ 0.8%; 0.015% ≤ Ti ≤ 0.2%; 0.005% ≤ Al ≤ 0.1%; 0% ≤ Cr ≤ 2.50%; 0% ≤ S ≤ 0.05%; 0% ≤ P ≤ 0.1%; 0% ≤ B ≤ 0.010%; 0% ≤ Ni ≤ 2.5%; 0% ≤ Mo ≤ 0.7%; 0% ≤ Nb ≤ 0.15%; 0% ≤ N ≤ 0.015%; 0% ≤ Cu ≤ 0.15%; 0% ≤ Ca ≤ 0.01%; 0% ≤ W ≤ 0.35%, the remainder being iron and unavoidable impurities resulting from the manufacture of the steel.
[0038] For example, the steel plate is 22MnB5 with the following weight composition: 0.20%≤C≤0.25%; 0.15%≤Si≤0.35%; 1.10%≤Mn≤1.40%; 0%≤Cr≤0.30%; 0.020%≤Ti≤0.060%; 0.020%≤Al≤0.060%; 0.002%≤B≤0.004%, and the remainder is iron and unavoidable impurities from the manufacture of steel.
[0039] In another embodiment, the steel plate has the following weight composition: 0.24%≤C≤0.38%; 0.40%≤Mn≤3%; 0.10%≤Si≤0.70%; 0.015%≤Al≤0.070%; Cr≤2%; 0.25%≤Ni≤2%; 0.015%≤Ti≤0.10%; Nb≤0.060%; 0.0005%≤B≤0.0040%; the remainder being iron and unavoidable impurities resulting from the manufacture of steel.
[0040] Alternatively, the steel plate may have the following weight composition: 0.30% ≤ C ≤ 0.40%; 0.5% ≤ Mn ≤ 1.0%; 0.40% ≤ Si ≤ 0.80%; 0.1% ≤ Cr ≤ 0.4%; 0.1% ≤ Mo ≤ 0.5%; 0.01% ≤ Nb ≤ 0.1%; 0.01% ≤ Al ≤ 0.1%; 0.008% ≤ Ti ≤ 0.003%; 0.0005% ≤ B ≤ 0.003%; 0.0% ≤ P ≤ 0.02%; 0.0% ≤ Ca ≤ 0.001%; 0.0% ≤ S ≤ 0.004%; 0.0% ≤ N ≤ 0.005%, with the remainder being iron and unavoidable impurities resulting from the manufacture of the steel.
[0041] In another embodiment, the steel plate has the following weight composition: 0.040%≤C≤0.100%; 0.80%≤Mn≤2.00%; 0%≤Si≤0.30%; 0%≤S≤0.005%; 0%≤P≤0.030%; 0.010%≤Al≤0.070%; 0.015%≤Nb≤0.100%; 0.030%≤Ti≤0.080%; 0%≤N≤0.009%; 0%≤Cu≤0.100%; 0%≤Ni≤0.100%; 0%≤Cr≤0.100%; 0%≤Mo≤0.100%, with the balance being iron and unavoidable impurities from the manufacture of steel.
[0042] In another embodiment, the steel plate has the following weight composition: 0.06%≤C≤0.1%, 1%≤Mn≤2%, Si≤0.5%, Al≤0.1%, 0.02%≤Cr≤0.1%, 0.02%≤Nb≤0.1%, 0.0003%≤B≤0.01%, N≤0.01%, S≤0.003%, P≤0.020%, less than 0.1% of Cu, Ni and Mo, and the remainder is iron and unavoidable impurities generated by the manufacture of steel.
[0043] In another embodiment, the steel plate has the following weight composition: 0.015%≤C≤0.25%; 0.5%≤Mn≤1.8%; 0.1%≤Si≤1.25%; 0.01%≤Al≤0.1%; 0.1%≤Cr≤1.0%; 0.01%≤Ti≤0.1%; 0%≤S≤0.01%; 0.001%≤B≤0.004%; 0%≤P≤0.020%; 0%≤N≤0.01%; the balance being iron and unavoidable impurities from the manufacture of steel.
[0044] Alternatively, the steel plate has the following weight composition: 0.2%≤C≤0.34%; 0.5%≤Mn≤1.24%; 0.5%≤Si≤2.0%; 0%≤S≤0.01%; 0%≤P≤0.020%; 0%≤N≤0.01%, the balance being iron and unavoidable impurities from the manufacture of steel.
[0045] In step B, the steel plate is cut into blanks. The coated steel blanks may have a non-uniform thickness. This is the case of so-called "custom rolled blanks" obtained by cutting a plate obtained by a rolling process with a variable force in the length direction of the plate. Or this may also be the case of so-called "custom welded blanks" obtained by welding at least two sub-blanks of different thickness.
[0046] In step C, the heat treatment of the blank is carried out at a temperature of 800° C. to 970° C., preferably 840° C. to 950° C. The blank is held during a dwell time of 1 minute to 15 minutes. During the heat treatment before press hardening, the coating forms an alloy layer having high corrosion resistance, wear resistance, abrasion resistance and fatigue resistance.
[0047] In step D, after heat treatment, the blank is then transferred to a press-hardening tool.
[0048] In step E, press hardening is performed at a temperature of 600°C to 830°C.
[0049] In step F, the part is cooled in the hot forming tool or after transfer to a special cooling tool. The cooling rate is controlled according to the steel composition in such a way that the final microstructure after press hardening is consistent with the target mechanical properties. After press hardening, the part can be tempered to achieve the target microstructure and mechanical properties.
[0050] In a preferred embodiment, the steel microstructure comprises at least 95% martensite by volume.
[0051] In another embodiment, after press hardening, the steel microstructure comprises, by volume fraction, at least 50% martensite and less than 40% bainite.
[0052] In another embodiment, after press hardening, the steel microstructure comprises, by volume fraction, 5 to 20% martensite, up to 10% bainite, and at least 75% equiaxed ferrite.
[0053] The coated component according to the invention is thus obtained by press hardening, but can also be achieved by any suitable combination of cold stamping and press hardening.
[0054] The component obtained in step F is covered with a surface oxide layer on its outer surface. This oxide layer contains aluminum, zinc and magnesium from the coating and iron from the steel matrix. During the heat treatment, the iron diffuses through the coating. The thickness of the oxide layer can vary between 0.2 μm and up to 3 μm, preferably between 0.3 μm and 1.5 μm. Near the surface, the oxidizable elements have their highest concentration. The ratio of the elements can be obtained by energy X-ray dispersion spectroscopy. Therefore, it gives the composition of a layer with a thickness of 1.5 μm from the outer surface.
[0055] According to the invention, the surface oxide layer comprises from 20 to 60% by weight, preferably from 25 to 50% by weight, of zinc.
[0056] According to the invention, the surface oxide layer optionally comprises 10 to 27%, preferably 17 to 24% by weight of aluminum.
[0057] According to the invention, the surface oxide layer optionally comprises 5 to 10% by weight of magnesium.
[0058] According to the invention, the surface oxide layer optionally comprises 10 to 28%, preferably 14 to 25% by weight of iron.
[0059] Without wishing to be bound by any theory, it is believed that the corrosion performance after the phosphating step is related to the zinc content in the surface oxide layer having a depth of 1.5 μm or less from the outer surface of the coating.
[0060] If less than 20 wt% zinc is present in the surface oxide layer, the surface consists mainly of non-phosphatizable aluminum oxide. It is believed that after phosphatization, the zinc oxide does not cover the upper surface sufficiently to ensure a suitable phosphate crystal layer, resulting in poor corrosion performance.
[0061] If more than 60 wt. % zinc is present in the surface layer, the surface becomes rough and the layer structure becomes inhomogeneous, as in Figure 2 This is believed to result in poor corrosion performance.
[0062] The invention is particularly relevant to the manufacture of any component that is relevant to a crash in a wet area. Specifically, the component may be a front rail, a seat cross member, a side sill member, a dash panel cross member, a front floor reinforcement, a rear floor cross member, a rear rail, a B-pillar, a door ring or a shotgun.
[0063] For automotive applications, the parts are pre-degreased and phosphated to ensure adhesion of the other layers. The parts are then immersed in an electrocoating bath, whereby the layers are formed on the parts by electrophoresis. After the electrocoating step, other coating layers can be deposited, such as primer, undercoat and topcoat of paint.
[0064] Typically, the thickness of the phosphate layer is 1 μm to 2 μm, and the thickness of the electrocoating layer is 15 μm to 25 μm, preferably less than or equal to 20 μm. The electrophoretic layer ensures additional protection against corrosion.
[0065] The invention will now be illustrated in experiments performed for reference only. The experiments are not limiting.
[0066] Example
[0067] For all samples, the steel plate used was 22MnB5. The composition of the steel was as follows: C = 0.23%; Mn = 1.2%; Si = 0.25%; %; Cr = 0.2%; Al = 0.04%; Ti = 0.04%; B = 0.003%.
[0068] All coatings were deposited by hot dip galvanizing process. The hot dip bath temperature was set at 620°C or 650°C.
[0069] Example 1: Surface analysis:
[0070] Thus, tests 1 to 13 were prepared as follows: the coated samples were cut into blanks. These blanks were then heated at a temperature of 900° C. during a dwell time varying between 5 and 6 minutes. The blanks were transferred to a press tool and hot stamped to obtain the components. Finally, the components were cooled to obtain hardening by martensitic transformation. After press hardening and when observed with a microscope, test 8 had a smoother surface and a homogeneous layer structure, as shown in Figure 1 This is also true for the other tests according to the invention. In contrast, tests 11 to 13 show a rough surface with an inhomogeneous layer structure, as in Figure 2 It can be seen above.
[0071] After the heat treatment, the test pieces were subjected to EDX testing to deliver their surface composition of the outer layer with a thickness of 1.5 μm: Surface analysis testing was used to determine the weight percentage of elements on the surface. After the heat treatment, the samples were analyzed using energy dispersive X-ray spectroscopy (EDX) at 15 kV to determine the surface atomic composition of the oxide layer. The results are summarized in Table 1.
[0072] Table 1: Tested samples
[0073]
[0074] *According to the test of the present invention, Underlined values Not according to the invention.
[0075] Example 2: Corrosion test
[0076] Degreasing of the samples was then achieved. This was followed by a phosphating step by immersing them in a bath solution containing ATCC® at 50° C. for 3 minutes. The composition of the phosphating bath was ATCC® from the supplier Chemetall. Products. Their concentrations are disclosed in Table 2.
[0077] Table 2: Component concentrations in phosphating baths
[0078]
[0079] The samples were then wiped with water and dried with hot air and finally stored in a corrosion chamber for 12 cycles in accordance with VDA 233-102.
[0080] After these cycles, all samples according to the invention had less than 20% red rust as a percentage of the surface.
[0081] Table 3: Corrosion results
[0082]
[0083] *According to the test of the present invention, Underlined values Not according to the invention.
[0084] Tests 1 and 11 to 13, whose steel sheet coatings respectively contained 5% and 15% by weight of zinc, also had less than 20% by weight or more than 60% by weight of zinc in the oxide layer after heat treatment. They showed more than 20% red rust in terms of area fraction.
[0085] The tests according to the invention showed less than 20% red rust in terms of area fraction.
Claims
1. A steel sheet coated with a metal coating, the metal coating comprising, by weight percentage: 7.5% to 9.0% zinc; 1.1% to 4.0% silicon; 1.1% to 8.0% magnesium; up to 3.0% iron; optionally an element selected from Pb, Ni, Zr, or Hf, each element having a content by weight of less than 0.3%; optionally up to 100 ppm calcium; and up to 0.02% unavoidable impurities, the balance being aluminum, and wherein the coating weight of the metal coating is 50 g / m2 for the sum of both sides of the steel sheet 2 Up to 500g / m 2 .
2. The steel sheet according to claim 1, wherein the metal coating comprises, by weight percentage: 7.5% to 9.0% zinc; 2.0% to 4.0% silicon; 1.1% to 4.0% magnesium; up to 3.0% iron; and optionally an element selected from Pb, Ni, Zr, or Hf, the content of each element by weight being less than 0.3%; optionally up to 100 ppm calcium; and up to 0.01% unavoidable impurities, the balance being aluminum.
3. The steel sheet according to claim 1 or 2, wherein the coating weight of the coating is 80 g / m2 for the sum of both sides of the steel sheet. 2 Up to 150g / m 2 .
4. A method for producing a hardened component coated with an anti-corrosion coating, comprising the steps of: A) providing a coated steel sheet according to any one of claims 1 to 3, B) cutting the coated steel sheet to obtain blanks, C) heat treating said blank at a temperature of 840° C. to 950° C. to obtain a fully austenitic microstructure in said steel, D) transferring the blank into a pressing tool, E) press-hardening the blank to obtain a component, F) Cooling the component obtained in step E) to obtain a press-hardened component.
5. A press-hardened coated steel part obtained by press-hardening a coated steel sheet according to any one of claims 1 to 3, the coating being covered on its outer surface with a surface oxide layer, such oxide layer containing 20 wt % to 60 wt % of zinc over a thickness of 1.5 μm from the outer surface of the coated part.
6. A press-hardened coated steel component according to claim 5, wherein such oxide layer comprises 25 to 50 wt. % zinc.
7. The press-hardened coated steel component according to claim 5 or 6, wherein the microstructure of the press-hardened component comprises at least 95% martensite in volume fraction.
8. The press-hardened coated steel component according to claim 5 or 6, wherein the microstructure of the press-hardened component comprises at least 50% martensite and less than 40% bainite in volume fraction.
9. A press-hardened coated steel component according to any one of claims 5 or 6, wherein the microstructure of the press-hardened component comprises 5% to 20% martensite, up to 10% bainite and at least 75% equiaxed ferrite.
10. Use of a component according to any one of claims 5 to 9 for the manufacture of a motor vehicle.
11. Use of a component according to claim 10 for producing a component located in the wet area of a motor vehicle.
12. Use of the component according to claim 11 for manufacturing at least one component selected from the group consisting of: front longitudinal beam, seat cross member, side member, dash cross member, front floor reinforcement, rear floor cross member, rear longitudinal beam, B-pillar, door ring, upper longitudinal beam.